2016
DOI: 10.1016/j.carbon.2016.06.072
|View full text |Cite
|
Sign up to set email alerts
|

Graphene and MoS2 interacting with water: A comparison by ab initio calculations

Abstract: Although very similar in many technological applications, graphene and MoS 2 bear significant differences if exposed to humid environments. As an example, lubrication properties of graphene are reported to improve while those of MoS 2 to deteriorate: it is unclear whether this is due to oxidation from disulfide to oxide or to water adsorption on the sliding surface. By means of ab initio calculations we show here that these two layered materials have similar adsorption energies for water on the basal planes. T… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

25
115
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 130 publications
(141 citation statements)
references
References 60 publications
25
115
0
1
Order By: Relevance
“…[33,34] Furthermore, the atomic structure of pristine-MoS2 also prevents water from intercalating between the layers due to the small interlayer distance, the lack of strong interlayer bonding sites for the water molecules and native oxides at the 6 edges. [15,40] Both pristine-MoS2 and graphene physically interact with water at the basal plane [35] and recent studies have suggested the formation of ice like water on the basal plane of other 2D materials. [41] Therefore the small increase in thickness of pristine-MoS2 by ~0.4nm is attributed to a single layer of water adsorbing on the pristine-MoS2 surface.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…[33,34] Furthermore, the atomic structure of pristine-MoS2 also prevents water from intercalating between the layers due to the small interlayer distance, the lack of strong interlayer bonding sites for the water molecules and native oxides at the 6 edges. [15,40] Both pristine-MoS2 and graphene physically interact with water at the basal plane [35] and recent studies have suggested the formation of ice like water on the basal plane of other 2D materials. [41] Therefore the small increase in thickness of pristine-MoS2 by ~0.4nm is attributed to a single layer of water adsorbing on the pristine-MoS2 surface.…”
Section: Resultsmentioning
confidence: 99%
“…MoS2 has a tri-layer atomic structure, where the Mo/S atoms can polarize more strongly than the monolayer carbon structure of graphene to physisorb water on to the surface. [35] The absorption energy of a water molecule on defect free monolayer MoS2 is reported to be -0.18eV compared to -0.15eV on graphene. [35] The adsorption energy is reported to further increase for thicker and defective MoS2.…”
Section: Role Of Water On Friction Of Pristine Ultrathin Mosmentioning
confidence: 99%
See 2 more Smart Citations
“…By tuning the pore creation process, Jang et al 24 have demonstrated nanofiltration membranes that reject small molecules but offer high permeance to water or monovalent ions. Also, studies have shown how defects, oxidation, and functionalization can affect the ionic blockage [25][26][27] All of these studies point to a near future where 2D membranes will have a major impact on desalination processes. In this work, we address the issue of the selectivity of the porous membrane.…”
Section: Introductionmentioning
confidence: 99%